Establishment, expansion and regeneration of aspen (Populus tremula) in the Torneträsk area, subarctic Sweden - Van Bogaert, Rik; Jonasson, Christer; De Dapper, Morgan; Callaghan, Terry V (Supplement to: Van Bogaert, R et al. (2010): Range expansion of thermophilic aspen (Populus tremula L.) in the swedish Subarctic. Arctic, Antarctic, and Alpine Research, 42(3), 362-375, https://doi.org/10.1657/1938-4246-42.3.362, 2010)
In subarctic Sweden, recent decadal colonization and expansion of aspen (Populus tremula L.) were recorded. Over the past 100 years, aspen became c. 16 times more abundant, mainly as a result of increased sexual regeneration. Moreover, aspen now reach tree-size (>2 m) at the alpine treeline, an ecotone that has been dominated by mountain birch (Betula pubescens ssp. czerepanovii) for at least the past 4000 years. We found that sexual regeneration in aspen probably occurred seven times or more within the last century. Whereas sexual regeneration occurred during moist years following a year with an exceptionally high June-July temperature, asexual regeneration was favored by warm and dry summers. Disturbance to the birch forest by cyclic moth population outbreaks was critical in aspen establishment in the subalpine area. At the treeline, aspen colonization was less determined by these moth outbreaks, and was mainly restricted by summer temperature. If summer warming persists, aspen spread may continue in subarctic Sweden, particularly at the treeline. However, changing disturbance regimes, future herbivore population dynamics and the responses of aspen's competitors birch and pine to a changing climate may result in different outcomes.